2008
DOI: 10.1021/jp711725e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Preferential Interaction Parameters by Multicomponent Diffusion. Applications to Poly(ethylene glycol)−Salt−Water Ternary Mixtures

Abstract: Poly(ethylene glycol) (PEG) is a hydrophilic nonionic polymer used in many biochemical and pharmaceutical applications. We report the four diffusion coefficients for the PEG-KCl-water ternary system at 25°C using precision Rayleigh interferometry. Here, the molecular weight of PEG is 20 kg mol -1 , which is comparable to that of proteins. The four diffusion coefficients are examined and used to determine thermodynamic preferential interaction coefficients. We find that the PEG preferential hydration in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 43 publications
(125 reference statements)
5
42
0
Order By: Relevance
“…Indeed, for ternary aqueous salt solutions containing a neutral macromolecule, it has been recently observed that only one of the two diffusioncoefficient ratios can be approximated as a thermodynamic factor. 7 In contrast, the other diffusion-coefficient ratio was found to be significantly smaller than its corresponding thermodynamic factor. This implies that frictional interactions cannot be generally neglected.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Indeed, for ternary aqueous salt solutions containing a neutral macromolecule, it has been recently observed that only one of the two diffusioncoefficient ratios can be approximated as a thermodynamic factor. 7 In contrast, the other diffusion-coefficient ratio was found to be significantly smaller than its corresponding thermodynamic factor. This implies that frictional interactions cannot be generally neglected.…”
Section: Introductionmentioning
confidence: 86%
“…This assumption has led to the examination of (D ij ) 0 /(D ii ) 0 strictly in terms of thermodynamic parameters. However, it has been experimentally observed for the poly(ethylene glycol) (1) 7 This implies that the thermodynamic approximation is valid only for the small solute (i ) 2).…”
Section: Behavior Of Cross-diffusion Coefficientsmentioning
confidence: 99%
See 3 more Smart Citations